A numerical assessment of the influence of Industry 4.0 technologies on the cognitive complexity of procedure-guided tasks. (5th October 2022) - Lucchese, Andrea; Facchini, Francesco; Mossa, Giorgio; Mummolo, Giovanni; Sisto, Francesco Paolo
In Industry 4.0 (I4.0) context, procedure-guided tasks are characterised by a greater complexity due to the higher cognitive nature. On one side, increasing information processing demand and more articulated decision-making processes are required in new factories. On the other side, different I4.0 technologies are available to support workers in work environments. In this regard, the entropy measures were adopted to evaluate how the cognitive complexity required by general procedure-guided tasks changes when the I4.0 technologies are implemented. Results show that the implementation of I4.0 technologies decreases the information processing demand of the task (estimated in bit/s), reducing the cognitive effort of operators. Furthermore, the numerical simulation shows that adopting I4.0 technologies, an operator is able to perform a task 20% more complex (estimated in bit). Consequently, the study conducted allowed to predict how the information processing demand of procedure-guided tasks can be affected by implementing I4.0 technologies.